Factors affecting splanchnic haemodynamics in Crohn's disease: a prospective controlled study using Doppler ultrasound. Issue 5 (1st November 1998) - Maconi, G; Parente, F; Bollani, S; Imbesi, V; Ardizzone, S; Russo, A; Porro, G Bianchi
Abstract : Background —Current knowledge on splanchnic haemodynamics in Crohn's disease is limited. Aims —To investigate which features of Crohn's disease affect splanchnic haemodynamics, and to establish whether portal vein (PV) and superior mesenteric artery (SMA) blood supply reflects clinical or biochemical activity of Crohn's disease. Methods —Seventy nine patients with Crohn's disease and 40 controls were evaluated by Doppler ultrasound (US). The mean velocity of PV and SMA flow, the volume of blood flow of the PV and SMA, and the resistance index of SMA were studied. A series of clinical, biochemical, and US variables including Crohn's disease activity index, serum C reactive protein concentrations, disease duration and its anatomical location, smoking habits, abdominal complications, and current medical therapy, as well as the maximum bowel wall thickness as measured by US, were determined. The relation between PV and SMA blood flow and these variables was assessed by univariate and multivariate analysis. Results —Patients with Crohn's disease had significantly higher PV and SMA flow and a lower SMA resistance index than controls. Stepwise multiple regression analysis identified bowel wall thickness and location of the disease as the main predictive variables of both PV and SMA blood flow variation, accounting for 36% and 45% of their variability, respectively. No relation was found between splanchnic haemodynamics and disease activity. Conclusion —A hyperdynamic mesenteric circulation does exist in Crohn's disease; however splanchnic blood flow does not reflect the clinical or biochemical activity of the disease, but seems to be linked more to other Crohn's disease characteristics, such as maximum bowel thickness and anatomical location.